Intradermal injection of umbilical cord mesenchymal stem cell was more effective than platelet rich plasma in increasing amount of collagen and fibroblasts in Wistar rats (Rattus norvegicus) back skin exposed to ultraviolet B rays - Anne Carolina Kencanawati; Wimpie Pangkahila; Anak Agung Gde Putra Wiraguna (Neurologico Spinale Medico Chirurgico, 2021)
Background: Ultraviolet B exposure is one of the causes of extrinsic skin aging. Ultraviolet exposure may lead to skin collagen damage. This study about mesenchymal stem cells from umbilical cord (UCMSC) compared with platelet rich plasma (PRP) with the aim was to prove that the intradermal injection of UCMSC was more effective than PRP in increasing amount of collagen and fibroblasts in Wistar rats' back skin exposed to Ultraviolet B rays. Methods: This study used post-test only control group design. Subjects were 36 Wistar rats aged 2.5 months. A control group consisting of 18 Wistar rats treated with intradermal injection of PRP and the treatment group with UCMSC. Both groups were exposed to UVB with a total radiation dose of 840 mJ/cm2. The parameter of collagen was determined by picro sirius red staining while fibroblasts by Haematoxylin-Eosin staining. Result: The mean amount of collagen in the control group was lower (57,82±6.52%) than the treatment group (65.69±4.51%) with p<0.001. The result showed there were differences in the number of collagen in both groups (p<0.05). The mean number of fibroblasts in the control group was lower (22.63±5.98 cell/field of view) than the treatment group (28.20±8.90 cell/field of view) with p=0.034. The result showed there were differences in mean of fibroblasts in both groups (p<0.05). Conclusion: It can be concluded that the intradermal injection of UCMSC was more effective in increasing the amount of collagen and fibroblasts than intradermal injection of PRP in Wistar rats' back skin exposed to UVB rays.